Genética populacional do ariocó Lutjanus synagris (Linnaeus, 1758) na costa brasileira - Pereira, Lougan Lagass (2016)
Ariocó (Lutjanus synagris) is a reef fish species of the Lutjanidae family that occurs from the USA East Coast in North Carolina to southern Brazil. Although this species presents high ecological and economic importance few studies about population genetic questions were developed. This study aimed to evaluate the genetic diversity and connectivity among individuals of the species L. synagris considering five different locations of Brazilian coast. Caudal fin samples of 94 individuals were obtained from fishmongers, this being 19 from Maranhao (MA), 32 from Paraiba (PB), 37 from Abrolhos Bank (AB), four from southern Espirito Santo (ES) and two from Sao Paulo (SP). The specie of Individuals was confirmed by experts, following the FAO (United Nations Food and Agriculture Organization) identification key. Fragments around 840bp of the control region of mitochondrial DNA (D-loop) were amplified and sequenced. Thirty-eight haplotypes were identified. The most frequent (haplotype 29) was shared by 43 individuals from the five sample units. The haplotype diversity was high, being the highest for SP (h = 1.00 +/- 0.50), and the lowest for BA (h = 0.74 +/- 0.08). The nucleotide diversity was low, being the highest for PB (π = 0.0025 +/- 0.0016), and the lowest for BA (π = 0.0015 +/- 0.0010). The results of AMOVA (Fst = - 0.01, P-value = 0.68 + - 0.016) indicated a single population with intense gene flow. The haplotype network showed a central haplotype shared by all sampling units. Tests of Neutrality (Fu and Tajima D) showed negative and significant values for all sampled units, except for SP. With these data it is possible suggest that the population has experienced at last two bottleneck events, with subsequent expansion. For the evaluated marker, the data suggest a single genetic stock, information that should be considered if a future species management plan is formulated.